Impact of Internet of Things, Cloud Computing, Artificial Intelligence, Digital Capabilities, Digital Innovation, IT Flexibility on Firm Performance in Saudi Arabia Islamic Bank - Alqahtani, Miad Murayh M; Singh, Harcharanjit; Haddadi, Essa Ali A; Al-Shibli, Fatema Salim Rashid; Al-balushi, Hanan Ahmed Abdullah (Advances in Social Sciences Research Journal, 2024)
This study delves into the impact of technological advancements on firm performance within the Islamic banking sector in Saudi Arabia, focusing on the roles of Internet of Things (IoT) capabilities, Cloud Computing Capabilities (CCC), and Artificial Intelligence (AI) capabilities. It explores how these technological dimensions influence operational efficiency, customer engagement, and competitive positioning, thereby affecting overall firm performance. The research further investigates the mediating role of digital innovation in translating technological capabilities into performance outcomes and examines the moderating effects of digital capabilities and IT flexibility on this relationship. Through empirical analysis, the study demonstrates that IoT, CCC, and AI capabilities are crucial drivers of firm performance, offering significant opportunities for process optimization, service innovation, and market differentiation. Digital innovation is identified as a key mediator that enables Islamic banks to harness the full potential of these technologies, suggesting that the strategic integration of digital innovation practices is vital for realizing performance gains. Additionally, the findings highlight the importance of robust digital capabilities and a flexible IT infrastructure in maximizing the benefits of technological advancements, underscoring their role in facilitating adaptation to technological changes and fostering a culture of continuous innovation. The study contributes to the literature on technology management and banking performance by providing insights into the strategic value of technological capabilities and digital innovation within the Islamic banking context. It offers practical implications for banking executives and policymakers in Saudi Arabia, emphasizing the need for a comprehensive approach that encompasses technological adoption, innovation management, and capability development to achieve enhanced firm performance in the digital era.